The Effect of Accreditation on Patient Satisfaction and Performance at a Community Health Center in Jayapura - Medyati, Novita; Zainuri, Agus (Jurnal Kesmas Prima Indonesia, 2025)
The implementation of accreditation in a community health center can have a positive impact with the existence of legal security related to the quality of services provided by the community health center. Therefore, it is important to measure several indicators for assessing the implementation of accreditation such as measuring satisfaction and performance in the community health center. The purpose of this study was to analyze the level of satisfaction and performance of the community health center at Community Health Center X, Jayapura City. This type of research is descriptive quantitative conducted in August 2024 with the research location at Community Health Center X in Jayapura City. The research subjects were patients visiting Community Health Center X. The sampling technique used accident sampling with a sample size of 72 respondents. Data analysis was descriptive and presented in the form of a frequency distribution. The results of the study found that the highest level of satisfaction of respondents was in the Satisfied category with an average value of 37.6 (52.2%), while the performance of health services at the Community Health Center was in the Good category. Based on the results of the study, it shows good quality services at Community Health Center X based on indicators of the level of satisfaction of service users and performance. To determine the extent of the contribution of accreditation to service quality, further research is needed.   Kata kunci: Akreditasi, Kepuasan, Kinerja, Puskesmas.